The sequential organization of Malaysian radio phone-in programmes / Siti Nurbaya Mohd Nor - Siti Nurbaya , Mohd Nor (2018)
This thesis examines the sequential organisation of Malaysian radio phone-in interactions. Based on data recorded from selected English radio phone-in programmes, the analysis applies the organisational properties and structures for social interaction in order to generate a formal description of phone-in interactions. Using the methodological approach of Conversation Analysis (CA), the study explores the sequential organization of interaction in the radio phone-in programmes. This involves the opening and closing sequences, the turn-validation and follow-up stages and the management of participation between radio hosts and callers. The thesis also deals closely with Harvey Sacksï¿½ (1992) work on the categorical and sequential organisation of talk and social action, as well as on previous works on radio phone-in interactions (Hutchby, 2001, 2006; Thornborrow, 2001a, 2001b; Fitzgerald, 1999; Fitzgerald and Housley, 2002; Ferencik, 2007; Dori-Haconen, 2012, 2014; Ames 2013). The second methodological approach adopted for the study is Membership Categorization Analysis (MCA). Calls to a radio phone-in programme is described as a membership categorization device, which is a locally relevant set of categories with associated rules for recognizing and applying these categorizations, that are generated in, and relevant for, situated instances of action (Sacks, 1992). The relevant set of categories is made possible by the hosts of the show as well as callers to the programme. These membership categories and activities are established and made relevant in the organisation of turns-at-talk and social action. Two sets of analysis are shown to illustrate the application of membership devices during the talk-in interactions. These are the programme relevant categories and the sequential use of categorical information. The former include the categorical devices employed by the host so as to be programme-relevant and callersï¿½ devices of call-relevant identities; while the latter refers to the categorical information of topic-relevant categories, topic-opinion categories and topic-generated categories. These categories contribute towards the accomplishment of particular contexts and action. The analysis considers the categorical and sequential organization of episodes of talk-in interactions, and discusses how an institutional order of talk is introduced, developed and accomplished in the course of the sharing of views and experiences. The thesis contributes to conversation analytic research on the sequential organization of talk-in-interaction, and focuses its attention to the categorical organization of sequences and action, and the sequential organization of categorization work. In offering a detailed analysis of phone-in interactions, and insight into the sequential and categorical organization of social action, the thesis makes a significant contribution to the fields of linguistics and media discourse.